Prey species increase activity in refugia free of terrestrial predators - Potash, Alex D.; Conner, L. Mike; Clinchy, Michael; Zanette, Liana Y.; McCleery, Robert A. (Oecologia, 2023)
The decline of terrestrial predator populations across the globe is altering top-down pressures that drive predator–prey interactions. However, a knowledge gap remains in understanding how removing terrestrial predators affects prey behavior. Using a bifactorial playback experiment, we exposed fox squirrels to predator (red-tailed hawks, coyotes, dogs) and non-predator control (Carolina wren) calls inside terrestrial predator exclosures, accessible to avian predators, and in control areas subject to ambient predation risk. Fox squirrels increased their use of terrestrial predator exclosures, a pattern that corresponded with 3 years of camera trapping. Our findings suggest fox squirrels recognized that exclosures had predictably lower predation risk. However, exclosures had no effect on their immediate behavioral response towards any call, and fox squirrels responded most severely to hawk predator calls. This study shows that anthropogenically driven predator loss creates predictably safer areas (refugia) that prey respond to proactively with increased use. However, the persistence of a lethal avian predator is sufficient to retain a reactive antipredator response towards an immediate predation threat. Some prey may benefit from shifting predator–prey interactions by gaining refugia without sacrificing a sufficient response towards potential predators.